2023
DOI: 10.3390/women3030030
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Post-Marriage Education and Employment among Bangladeshi Women: A Cross-Sectional Analysis

Abstract: Higher education and employment are two key components of women’s empowerment. However, many women fail to continue their studies or work after marriage, which can significantly reduce their empowerment potential, especially in countries with stark gender inequality such as in Bangladesh. In this study, our objective was to explore the individual, household and community factors associated with post-marriage education and employment among Bangladeshi women using data from the latest Bangladesh Demographic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…26 Earlier research on post-nuptial continuation of education among women in Bangladesh mainly focused on some individual-level variables, such as age at marriage, childbirth, owning a cell phone, or better sanitary conditions. 27 28 Bhowmik et al revealed that women who married before age 18 and adolescent mothers were less likely to continue education after marriage. 27 Although Ghose et al's study in Bangladesh demonstrated that communitylevel variables have a significant effect on women's postmarital education, their analysis only took into account region and place of residence.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…26 Earlier research on post-nuptial continuation of education among women in Bangladesh mainly focused on some individual-level variables, such as age at marriage, childbirth, owning a cell phone, or better sanitary conditions. 27 28 Bhowmik et al revealed that women who married before age 18 and adolescent mothers were less likely to continue education after marriage. 27 Although Ghose et al's study in Bangladesh demonstrated that communitylevel variables have a significant effect on women's postmarital education, their analysis only took into account region and place of residence.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%